Kualitas Pelayanan Publik terhadap Peningkatan Kinerja Aparatur di Kantor Kelurahan Benteng Kecamatan Baranti Kabupaten Sidenreng Rappang - Kamarudding Sellang; Abdul Useng (PRAJA: Jurnal Ilmiah Pemerintahan, 2028)
Abstract Public service is all service activities undertaken by public service providers as addressing the needs of the public. In the public service, government officials responsible for providing the best service to the community in order to create a welfare society. Public services should be based on certain standards. Standards of public service is a standard size or requirements that must be met in the public service and must be adhered to by the provider (the government) and or service users (public). Every public service should have a service standard and published as a guarantee of certainty for service recipients. complaints from the public. Behavioral apparatus especially those who are on the cutting edge of public service, often giving the impression of less sympathetic service, slow, and synonymous with money. Keywords: quality, public service, the performance of the apparatus